Conservation Policy: Helping or hindering science to unlock properties of plants and fungi. Issue 5 (29th September 2020) - Williams, China; Walsh, Alexandra; Vaglica, Valentina; Sirakaya, Aysegül; da Silva, Manuela; Dalle, Gemedo; Winterton, Deborah; Annecke, Wendy; Smith, Paul; Kersey, Paul J.; Way, Michael; Antonelli, Alexandre; et al.
Societal Impact Statement: Biodiversity loss is happening at an unprecedented rate. Understanding and protecting biodiversity has never been more urgent, and scientific research is key to this. Fair and transparent access and benefit sharing policies enable research to take place, whilst supporting sustainable livelihoods of communities and ensuring benefits are shared. Current national legislation has been unevenly implemented and, in this article, we recommend frameworks be developed to standardize the provision and use of genetic resources for non‐commercial research. Summary: Access to genetic resources for scientific research is vital to support and promote the conservation and sustainable use of the world's biodiversity. The regulatory framework for research is stipulated by Access and Benefit Sharing (ABS) legislation at a national level, but other elements – legal transparency, respect, cooperation, and trust – are essential for its effective and sustainable implementation. Despite the intention of this "ABS regime" to protect natural resources and associated knowledge from misappropriation, several studies have questioned whether national regulatory approaches have led to constraints on research and conservation. We analyse evidence and provide case studies on how these regulations are affecting research. We find that the number of Internationally Recognized Certificates of Compliance (IRCC) of the Nagoya Protocol (NP), the key compliance mechanism of the ABS system, doubled in the six months prior to February 2020 and analyse why this may be the case. Additionally, a survey of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Authorities in 28 countries, found differences in the way the Registered Scientific Institute scheme is interpreted and used to facilitate scientific research. Our results suggest while the regulatory systems are perceived as hindering research and conservation, regulatory mechanisms enabling responsible research are becoming increasingly functional. We argue that functional and transparent systems are needed for both regulators and researchers, to ensure that non‐commercial research can continue smoothly, and present conclusions to support research for the benefit of all countries and partners involved, through appropriate frameworks for implementation and reporting. Abstract : Biodiversity loss is happening at an unprecedented rate. Understanding and protecting biodiversity has never been more urgent, and scientific research is key to this. Fair and transparent access and benefit sharing policies enable research to take place, whilst supporting sustainable livelihoods of communities and ensuring benefits are shared. Current national legislation has been unevenly implemented and, in this article, we recommend frameworks be developed to standardize the provision and use of genetic resources for non‐commercial research.